1997
DOI: 10.1126/science.276.5320.1839
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen on Ganymede: Laboratory Studies

Abstract: To test proposals for the origin of oxygen absorption bands in the visible reflectance spectrum of Ganymede, the reflectance of condensed films of pure oxygen (O2) and O2-water mixtures and the evolution of O2 from the films as a function of temperature were determined. Absorption band shapes and positions for oxygen at 26 kelvin were similar to those reported for Ganymede, whereas those for the mixtures were slightly shifted. The band intensity dropped by more than two orders of magnitude when the ice mixture… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
46
0

Year Published

1997
1997
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(55 citation statements)
references
References 32 publications
9
46
0
Order By: Relevance
“…Further, the relative band depths for pure 0 2 are not a good match to the Ganymede spectra. In the spectrum for the 02/ H20 mixture in Figure 1 of Vidal et al [1997], the combination of absorption peak positions and relative band depths appear to this author most similar to the telescopic data. In both papers the relative band depths are ignored.…”
Section: Introductionsupporting
confidence: 64%
See 1 more Smart Citation
“…Further, the relative band depths for pure 0 2 are not a good match to the Ganymede spectra. In the spectrum for the 02/ H20 mixture in Figure 1 of Vidal et al [1997], the combination of absorption peak positions and relative band depths appear to this author most similar to the telescopic data. In both papers the relative band depths are ignored.…”
Section: Introductionsupporting
confidence: 64%
“…Hence the suggestion of Calvin et al [1996] and Johnson and Jesser [1997] (see appendix below) that the 02 exists as radiation-induced inclusions (bubbles) in the icy surface. In BB and in an earlier paper [Vidal et al, 1997], they concluded that the 02 is not trapped in inclusions in the ice. Rather, it was suggested that solid 02 exists on Ganymede either in surface regions with very low temperatures or as 02 ice crystals in Ganymede's atmosphere.…”
Section: Introductionmentioning
confidence: 91%
“…Spectral absorption suggestive of ozone has been detected by the Galileo UVS on Ganymede (Hendrix et al, 1999) and by the Hubble Space Telescope on Ganymede, Rhea, and Dione (Noll et al, 1996b;Noll et al, 1997). Laboratory results are not entirely consistent with Galilean satellite observations, however (Vidal et al, 1997 andBahr, 1998), so being able to compare oxygen chemistry at a variety of temperatures and radiation environments will help in understanding the processes.…”
Section: Surface Composition and Chemistrymentioning
confidence: 85%
“…Contamination by trapped atmospheric O 2 or CO 2 was thought to be low but possibly was not. More recent experiments (Vidal et al 1997, Baragiola andBahr 1998) suggest varied but lower O 2 yields. Baragiola et al (1999) report only small upper limits for direct production of trapped O 2 within ice by 60 keV O + 2 (G O 2 < 5 × 10 −4 ) and 100 keV H + (G O 2 < 4 × 10 −5 ), but higher yields are possible (Johnson 1999).…”
Section: Fig 15mentioning
confidence: 95%